Social support and breastfeeding practices: a cross-sectional study (Research, Society and Development, 2020)
Aim: to verify the association between social support and the practice of exclusive breastfeeding until the third month of life of the infant. Methods: a cross-sectional study was conducted in a prospective cohort study, with mothers and children born in a public hospital in Rio Grande do Sul. Data collected up to 48 hours after delivery and in the baby's third month of life on home visits were used. Data on socioeconomic classification, maternal age, prenatal care and infant feeding were evaluated and the Social Support Scale validated for Portuguese was applied. Data collection took place from July 2017 to October 2018. Results: 47 nursing mothers were interviewed in the first 48 hours postpartum and in the infant's third month of life. It was found that 24 (51.1%) infants were exclusively breastfeeding in the third month of life, followed by 12 (25.5%) in the absence of breastfeeding and 11 (23.3%) in mixed and complementary breastfeeding. Emotional support showed a statistically significant association (p